Difusi Inovasi Pelayanan Publik melalui Layanan SKCK Online di Polres Kota Serang - Salldy Marta Effendi; Titi Setiawati (Epistemik Press, 2026)
The implementation of the Online Police Clearance Certificate (SKCK) represents an information technology–based public service initiative at the Serang City Police Department. This innovation is intended to enhance the quality of public services while simplifying the application process for individuals applying for an SKCK. Accordingly, this study aims to examine the diffusion process of the online SKCK service innovation within the Serang City Police Department. This research adopts a descriptive qualitative approach. Data were collected through observations, document analysis, and in-depth interviews with selected informants. The informants were determined using purposive sampling, targeting individuals with substantial knowledge and involvement in the online SKCK service innovation. To ensure data validity, triangulation techniques were applied. The data analysis process involved data condensation, data display, and the drawing of conclusions. The findings reveal that the diffusion of the online SKCK service innovation at the Serang City Police Department unfolds through several key stages: (1) service innovation, (2) communication channels, (3) time dimension, and (4) social system.Keywords: Diffusion of Innovation, Public Service, Online Police Clearance Certificate (SKCK)